African Ancestry is a Risk Factor for Asthma and High Total IgE Levels in African Admixed Populations. Issue 4 (2nd April 2013) - Vergara, Candelaria; Murray, Tanda; Rafaels, Nicholas; Lewis, Rachel; Campbell, Monica; Foster, Cassandra; Gao, Li; Faruque, Mezbah; Oliveira, Ricardo Riccio; Carvalho, Edgar; Araujo, Maria Ilma; Cruz, Alvaro A.; et al.
ABSTRACT Characterization of genetic admixture of populations in the Americas and the Caribbean is of interest for anthropological, epidemiological, and historical reasons. Asthma has a higher prevalence and is more severe in populations with a high African component. Association of African ancestry with asthma has been demonstrated. We estimated admixture proportions of samples from six trihybrid populations of African descent and determined the relationship between African ancestry and asthma and total serum IgE levels (tIgE). We genotyped 237 ancestry informative markers in asthmatics and nonasthmatic controls from Barbados (190/277), Jamaica (177/529), Brazil (40/220), Colombia (508/625), African Americans from New York (207/171), and African Americans from Baltimore/Washington, D.C. (625/757). We estimated individual ancestries and evaluated genetic stratification using Structure and principal component analysis. Association of African ancestry and asthma and tIgE was evaluated by regression analysis. Mean ± SD African ancestry ranged from 0.76 ± 0.10 among Barbadians to 0.33 ± 0.13 in Colombians. The European component varied from 0.14 ± 0.05 among Jamaicans and Barbadians to 0.26 ± 0.08 among Colombians. African ancestry was associated with risk for asthma in Colombians (odds ratio (OR) = 4.5, P = 0.001) Brazilians (OR = 136.5, P = 0.003), and African Americans of New York (OR: 4.7; P = 0.040). African ancestry was also associated with higher tIgE levels among Colombians (β = 1.3, P = 0.04), Barbadians (β = 3.8, P = 0.03), and Brazilians (β = 1.6, P = 0.03). Our findings indicate that African ancestry can account for, at least in part, the association between asthma and its associated trait, tIgE levels.